Peripheral levels of brain-derived neurotrophic factor and S100B in neuropsychiatric systemic lupus erythematous. (November 2018) - Noris-García, E; Arce, S; Nardin, P; Lanigan, ME; Acuña, V; Gutierrez, F; Robinson-Agramonte, MA; Gonçalves, C-A
Background: The aim of this study was to investigate serum S100B and brain-derived neurotrophic factor (BDNF) in systemic lupus erythematous (SLE) patients, with and without neuropsychiatric (NP) manifestation activity. Methods: We assessed 47 SLE patients and 20 selected healthy individuals. Disease activity was assessed according to the SLE disease activity index (SLEDAI). Serum BDNF and S100B were measured by enzyme-linked immunosorbent assay. Results: Serum S100B protein was significantly higher in SLE patients. BDNF levels were significantly decreased in active SLE, when compared with inactive SLE, but not when compared with controls. S100B was clearly higher in the NPSLE group, when compared with the non-NPSLE or control groups. Receiver operating characteristic analysis of S100B revealed an area under the curve of 0.706 that discriminated NPSLE patients with peripheral polyneuropathy. Conclusions: Our findings reinforce the use of serum S100B as a biomarker in SLE, particularly for NPSLE. Moreover, we found a strong association between serum S100B and peripheral neuropathy, indicating a specific utility for this biomarker in SLE that warrants clinical investigation.